2006
DOI: 10.1097/01.mpg.0000228103.89454.a2
|View full text |Cite
|
Sign up to set email alerts
|

Esomeprazole‐Based 1‐Week Triple Therapy Directed by Susceptibility Testing for Eradication of Helicobacter pylori Infection in Children

Abstract: Esomeprazole-based 1-week triple therapy directed by susceptibility testing is highly effective for eradication of H. pylori infection in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
(41 reference statements)
0
25
2
Order By: Relevance
“…At present, in the pediatric population, five randomized studies have evaluated whether consumption of probiotics could increase H. pylori eradication rates and reduce the side effects of treatment (36)(37)(38)(39)(40).These trials do not provide evidence on the beneficial effect in children of supplementation of probiotics to triple therapy for eradicating H. pylori infection nor for positively (16,19,(43)(44)(45)(46) S: sensitive; R: Resistant affecting therapy-related symptoms and overall treatment tolerance. However, the five studies are all based on relatively small samples and lack the statistical power necessary to detect an important effect of the probiotics.…”
Section: Finland! Multicentermentioning
confidence: 99%
See 1 more Smart Citation
“…At present, in the pediatric population, five randomized studies have evaluated whether consumption of probiotics could increase H. pylori eradication rates and reduce the side effects of treatment (36)(37)(38)(39)(40).These trials do not provide evidence on the beneficial effect in children of supplementation of probiotics to triple therapy for eradicating H. pylori infection nor for positively (16,19,(43)(44)(45)(46) S: sensitive; R: Resistant affecting therapy-related symptoms and overall treatment tolerance. However, the five studies are all based on relatively small samples and lack the statistical power necessary to detect an important effect of the probiotics.…”
Section: Finland! Multicentermentioning
confidence: 99%
“…There is very limited information on the impact of clarithromycin and metronidazole resistance on H. pylori eradication in children. We have identified few clinical trials over the last two decades which evaluate the clinical outcome of H. pylori triple therapies with respect to pre-treatment susceptibility testing to clarithromycin and metronidazole (16,19,(43)(44)(45)(46). Despite the very limited number and power of pediatric clinical trials including susceptibility testing, the effect of resistance on treatment outcome was more pronounced for clarithromycin than for metronidazole (Table II).…”
Section: Factors Affecting Eradication Ratementioning
confidence: 99%
“…[3][4][5][6][7][8] To avoid, induction of secondary resistance in the infecting H. pylori strains, as well as further expensive and risky investigations, eradication treatment should reach at least 90% in per-protocol analysis. [14][15][16] In adults, increasing the duration of the triple therapy from 7 to 10 or 14 days improves the eradication rate by 4% and 5%-6%, respectively. [11][12][13] It has been shown that the sequential treatment performs slightly better than a standard (not tailored to antimicrobial susceptibility) triple therapy given for only 7 days.…”
Section: Introductionmentioning
confidence: 99%
“…Using a combination of PPI, amoxicillin, and metronidazole the eradication rate was 66.7 % [361]. However, if the triple therapy was based on an antibiogram, eradication can be achieved in > 90 % of the cases [430]. Culturing of the bacteria from a gastric biopsy with subsequent resistance testing is currently the procedure of choice.…”
Section: Which Diagnostic Tests Are Suitable?mentioning
confidence: 99%
“…A one week triple therapy of PPI plus amoxicillin and either clarithromycin or metronidazole at a sufficiently high dose and according to the results of the antibiotic sensitivity test is the therapy of choice for children and adolescents with confirmed Helicobacter pylori infection (Recommendation grade B, evidence level 2b, strong consensus). Comment: An eradication rate of > 90% can be reached with a one week triple therapy based on an antibiogram if there is no double resistance to clarithromycin and metronidazole [430]. For amoxicillin 50 mg/kg body weight and for clarithromycin and metronidazole 20 mg/kg body weight each given in 2 doses is considered a sufficiently high daily dose with in vitro sensitive pathogens.…”
Section: Which Diagnostic Tests Are Suitable?mentioning
confidence: 99%